The Impact of The Group Discussion Dethod on Attitudes of Responsibility and The Indonesian Language Learning Process for Class IX - Utami, Tiara Puji; Markhamah, M (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research aims to define the impact or results of applying the group discussion method on the responsible attitudes of class XI students. This research also aims to define the influence of the group discussion method on students' learning understanding outcomes. The method used in this research is a qualitative descriptive method, using interviews and direct observation as the data collection process. The data obtained is then analyzed according to considerations and visible results. The learning process is an important thing in education, in the learning process students learn many new things that they do not yet have. In a learning process, students not only gain cognitive knowledge, but also affective abilities are taken into account. The group discussion method has a good impact on the student learning process in class, because by using the discussion method students are able to improve their ability to express their thoughts and socialize. The group discussion method also has an influence on students' responsible attitudes towards their group friends and themselves.